Pengendalian Kualitas dengan P-Chart dan Pendekatan 5 WHYS pada Produk Second Bussines - Isya Nursa'iid, Arda Maulana; Sukanta, Sukanta (Fakultas Teknik Universitas Tulang Bawang, 2025)
This study aims to analyze and reduce the defect rate in products of the Secondary Business unit at PT. AX using the Six Sigma method with the D-M-A-I-C approach (Define, Measure, Analyze, Improve, Control). Analysis using a control chart (P-Chart) identified that the product defect rate reached 0.25%, with the main types of defects being bubble (40%), stone, drip, knot, and tin. The root causes of the product defects were identified through the 5 Whys approach, which revealed factors such as ineffective raw material drying and inadequate quality control. Improvements were made by enhancing operator training, technical supervision, the use of quality control tools, and the development of SOPs. Continuous control was implemented through routine monitoring, internal audits, and regular training. The results of the study demonstrate that the application of the Six Sigma method effectively reduces the product defect rate and improves the stability of the production process. Keywords: Product Defect, Quality Control, Six Sigma